(3GdMeGjI GdOHdheGSjI aj GdbGfhf GdOhdj GdeYGUQ (B/ s - (3YHOGddg CMeO YHO GdbGOQ ShjO GdYQHjs; (3UdGM GdOjf YGeQ (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2006)
(3jNdU ehVhY GdQSGdI ai GdMeGjI GdOHdheGSjI hgi JYfi JONd GdTNU GdbGfhfi GdOhdi dMeGjI QYGjGg JLGg TNU Ohdi GNQ GQJcH aYdG ZjQ eTQhY OhdjG JQJH Ydjg VQQG dgDdGA GdQYGjG hgi JKHJ ddOhdI GdJi jMed GdeVQhQ LfSjJgG (B: (3hdgG hSGFd deHGTQJgG bO Jchf SjGSjI Gh bVGFjI (B: (3hdGHO ef JhGaQ TQhW eYjfI deHGTQJgG aVdG Yf JhGaQ TQhW GdeSFhdjI GdOhdjIs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2006.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B640 - 653.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOhdj GdYGes; (3GdMeGjI GdOHdheGSjIs; (3bGYOI GdCjOi GdfXjaIs; (3GdeSFhdjI GdOhdjIs; (3GSJfaGO WQb GddLhA GdOGNdjIs; (3GdGdJRGeGJ GdOhdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs